Prevalence of Escherichia coli strains in horticultural farms from Argentina: antibiotic resistance, biofilm formation, and phylogenetic affiliation - Pellegrini, María Celeste; Okada, Elena; Gonzalez Pasayo, Ramon Alejandro; Ponce, Alejandra Graciela (Springer, 2022)
Escherichia coli is the bacteria most commonly used as an indicator of fecal contamination in agricultural environments. Moreover, E. coli is categorized as a priority pathogen due to its widespread antibiotic resistance. This study aimed to characterize E. coli strains isolated from 10 horticultural farms. Isolates were obtained from samples of vegetable crops (n = 62), the surrounding soil (n = 62), poultry litter (n = 8), and groundwater (n = 6). Phyllo-grouping assignment was performed on the total of E. coli isolates. Antibiograms and quantification of the minimal inhibitory concentration (MIC) were performed with antibiotics commonly used in humans. Biofilm formation capacity was studied by quantifying cells attached to culture tubes. Overall, 21 E. coli isolates were obtained. Three phylogenetic groups (A, B1, and C) and two Escherichia clade IV and IV–V were identified in the collection by polymerase chain reaction. Sixty-seven percent of the E. coli isolates were resistant to amoxicillin-clavulanic acid and/or ampicillin. Amoxicillin MIC values ranged from 11.9 to >190.5 µg/mL and ampicillin MIC values ranged from 3 to >190.5 µg/mL. All the E. coli isolates, resistant and non-resistant, had biofilm forming capacity. The presence of phenotypic resistance on fresh produce and environmental matrices could present significant opportunities for contamination that result in health risks for consumers. To the authors’ best knowledge, this is the first environmental assessment of resistant E. coli occurrence in horticultural farms in South America.